Computer vision syndrome among students during remote learning periods: harnessing digital solutions for clear vision - Muna Abed Alah (14779534) (2023)
Aim This study aimed to assess the prevalence of Computer Vision Syndrome (CVS) among children and adolescents in Qatar during the period of remote learning and explore the associated factors and discuss some digital health remedies that might reduce the risk. Methods We conducted an analytical cross-sectional study between June and August 2022 by collecting data via telephone interviews with parents of selected students utilizing the Computer Vision Syndrome Questionnaire (CVS-Q). Results We completed 1,546 interviews. The mean age of the students was (11 ± 2), male: female ratio was almost 1:1. About one quarter (368, 23.8%) of parents reported a previous diagnosis of visual disturbances among their children with over 88% of them wearing eyeglasses or medical contact lenses. The prevalence of CVS in our sample was about 8% (95%CI: 6.8–9.6). Mother’s employment, having positive history of visual disturbances, and excess screen time were found to be significant predictors of CVS. Conclusion Health care providers in collaboration with teachers should provide parents with evidence-based strategies to prevent or minimize the digital eye strain among students. In the landscape of remote learning, the implementation of digital remedies emerges as a proactive approach to mitigate the risk of digital eye strain. Other Information Published in: Frontiers in Public Health License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.3389/fpubh.2023.1273886